Broadband wireless communications : 3G, 4G, and wireless LAN - Wang, Jiangzhou (Kluwer international series in engineering and computer science, 2001)
Annotation The broadband wireless communications field is growing at an explosive rate, stimulated by a host of important emerging applications ranging from 3G, 4G and wireless LAN. For system planners and designers, the projections of rapidly escalating demand for such wireless services present major challenges and meeting these challenges will require sustained technical innovation on many fronts. The aim of this book is to provide a R & D perspective on the field of broadband wireless communications by describing the recent research developments in this area and also by identifying key directions in which further research is needed.